Horses for courses. (Economist, 2016)
The article discusses the impact of the end of Moore's law to the computer industry, presenting the views of various people from the technology sector on complexity of the computer industry without Moore's law. Pentium chip designer Bob Colwell, Greg Yeric of ARM, and technology analyst Linley Gwennap mention the importance of Moore's law and how its slow down forces technology firms to make choices between power, performance and cost.